Study of Acute Toxicity of Organotin Tributyltin Chloride on the Freshwater Bivalve Mollusc, Lamellidens marginalis from Godavari River at Maharashtra State, India - K.B. Shejule, J.T. Jagtap* (Recent Research in Science and Technology, 2010)
TBT is released from the antifouling paint into water due to the low water solubility, the TBT-compounds are rapidly adsorbed to suspended matter and deposit in the water bodies. The active substance TBT is highly toxic and also damaging to a multitude of non target species. The bivalves have been used for many years to determine the pollution status of water. Static bioassays were performed on bivalve, Lamellidens marginalis to evaluate the median lethal concentrations of TBTCl (tributyltin chloride) for 24, 48, 72 and 96 hrs. The LC50 values were 4.65, 3.39, 2.65 and 1.72 after 24, 48, 72 and 96 hrs. respectively. The results show that the LC50 values decreased with increase in exposure period.